THE EFFECT OF ANTIEMETIC FOR GALACTOGOGUE - Rahani, Sukma Marthia; Sjaaf, Amal Chalik (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Breastmilk provides nutrition that newborn and baby need during early stage of their lives. Breastmilk production can be increased by giving the mother oxytocin or prolactin enhancement that called galactogogue during breastfeeding. Giving galactogogue to mother bring side effect such as nausea, vomit, and insomnia. The example of galactogogue are domperidone and metoclopramide. Domperidone and metoclopramide not only useful to increase the breastmilk production as galactogogue but also can be used as antiemetic to reduce the effect in the galactogogue. This study aims to examine the effect of antiemetic for galactogogue during breastfeeding. Methods: This study was a systematic review that used PRISMA guidelines. Data obtained from Electronic databases ProQuest and Google Scholar that published between 2015 and 2018. By using keywords such as effect, antiemetic, galactogogue to find the relevant journal. Results: The search found 58 studies, of which 7 studies were relevant to analyze in this study. Majority of these studies used Randomized Control Trial (RCT) and 1 study used case study. Analysis of the studies found out that domperidone and metoclopramide can be used as antiemetic for galactogogue. Domperidone was not enter the blood circulation and did not interfere the breastmilk production